Exploring demand and supply sides of sharing economy of skills - LA, Soo Jung (KDI School, 2018)
Sharing Economy is a recently emerged economic system with a wide scope of industries. Existing literature provide insights to consumer behaviors in finance, automobile, and commodities sector but lack findings in the aspect of skills. This study attempts to explore the effects different variables exert on consumer and producer behaviors in skills sharing practices. The variables this study examines are transaction utility, social utility, sustainability utility, emotional utility, economic utility, trust utility, all of which affect the attitudes of consumers and producers. Then, this study divides consumers and producers into two different categories: potential and actual. As potential consumers and producers have no relevant experience in skills sharing practices, this study explores the effect of their attitudes on their intention, which then affects their satisfaction when an actual consumption or supply of a service takes place. For actual consumers and producers, this study explores the effect of attitude on satisfaction, a variable that affects loyalty towards, or a constant use of, a particular service. A survey is conducted on a randomly selected sample in Republic of Korea. The data analysis methods conducted in this study are factor analysis, multiple regression analysis, logit regression analysis and MANOVA. The difference in statistical significance of results for different groups of consumers and suppliers provides important insights for policy implications and managerial implications.
Thesis(Master) --KDI School:Master of Public Policy,2018